The Influence of the Thermodynamic Equilibrium Model of the Fe-M-C-N System on the Results of Calculations of Carbonitride Precipitation Kinetics - Marynowski, P.; Hojny, M. (Archives of Foundry Engineering, 2026)
The microalloying elements such as: Ti, Nb, V are added into steels to control their microstructure and mechanical properties. High chemical affinity of these elements for interstitials (N, C) results in precipitation of binary compounds, nitrides and carbides and products of their mutual solubility product – carbonitrides. Influence of carbonitrides on the microstructure and mechanical properties depends on their basic stereological parameters: volume fraction, VVvv, and their size, rr. Proper analysis of the carbonitride precipitation kinetics and the influence of the steel chemical composition on the parameters of M(C,N) carbonitride precipitates formed under isothermal conditions and on the precipitation hardening effect is important in the process of modelling the microstructure and mechanical properties of microalloyed steels. The paper presents a comparison of two thermodynamic equilibrium models: Adrian and Maugis-Gouné, and their impact on the results of calculations of carbonitride precipitation kinetics.